Determination of band tail widths in MOCVD grown InGaN single layer within GaN based p-i-n LED structure through photo-induced measurements - Ozdemir, Orhan; Bozkurt, Kutsal; Kuruoglu, Neslihan Ayarci; Bas, Hanife; Sarcan, Fahrettin; Erol, Ayse; Alshehri, Bandar; Dogheche, Karim; Dogheche, Elhadj (ELSEVIER, 2023)
Within a p-i-n LED structure, energy band gaps of MOCVD grown %10 In content InGaN and GaN layers were obtained through traditional UV-Visible transmission-absorption measurements and utilizing surface photo -voltage (SPV) and spectral photoconductivity (SPC) measurements. Moreover, all applied techniques determined that the total band offset between InGaN and GaN layers were around 0.3-0.4 eV. Furthermore, the temperature dependence of band gaps of each InGaN and GaN layer was analyzed through a modified Varshni relation where both Varshni coefficients and band tail energy width were explored. Band tails in a modified Varshni relation, SPV and SPC measurements were in agreement with each other and originated Franz-Keldysh Effect attributed to the presence of photon assisted tunneling.
Keywords: Surface photo -voltage; Spectral photo -conductivity; InGaN layer; Franz-Keldysh effect; TEMPERATURE-DEPENDENCE; CAPACITANCE-VOLTAGE; PHOTOVOLTAGE; Optics